Factors Influencing Malaysian University Students' Intention to Use Online Payment Systems : An Application of the Extended Perceived Value Theory - Yang, Tian; Chan, Tak Jie; Asmaul Husna, Haris Fadzilah; Ng, Miew Luan; Sharifah Sofiah, Syed Zainudin; Farhana Muslim, Mohd Jalis (Journal of Logistics, Informatics and Service Science (JLISS), 2024)
The current study aims to investigate the factors influencing the adoption of online payment systems among university students in Malaysia by extending the Perceived Value Theory (PVT). The research model incorporates perceived functional value, perceived social value, trust, and personal innovativeness as predictors of attitude, which in turn influences the intention to use online payment systems. A quantitative research design was employed, and data were collected from 395 university students in Malaysia using an online survey. The results, analyzed using PLS-SEM, revealed that perceived functional value, perceived social value, and trust significantly influence attitude, while personal innovativeness does not. Furthermore, attitude was found to be a significant predictor of the intention to use online payment systems. The findings provide valuable insights for online payment service providers and policymakers to promote the adoption of cashless payment methods among university students. However, the study has limitations, such as the cross-sectional design and the focus on a specific population, which future research should address. Keywords: Attitude, intention to use, online payment systems, Perceived Value Theory, personal innovativeness, trust, Industry, innovation and infrastructure